Drafting a Health and Safety Guide for Construction Forensics Practitloners - A. E. Fomenko (Теория и практика судебной экспертизы)
Presented is a draft occupational health and safety manual for construction forensics practitioners. The draft guide was developed with the purpose of improving the reliability of workplace health and safety arrangements in construction forensics units within the system of the Russian Ministry of Justice. The expert community is invited to consider the proposed draft document.